Strategi Komunikasi Pemasaran Spedometer Listrik Terhadap Masyarakat Pengguna Baru Di PT Srikandi Berkah Abadi Ponorogo - Sri Hartono; Nanang Cendriono; Ita Yogi Pratama (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
PLN is a monopoly trading company that sells electrical energy sources and manages all aspects of electricity in Indonesia, especially the Ponorogo area. In Ponorogo there is a company under the auspices of the Indonesian Electrical and Mechanical Contractors Association (AKLI) with the company name PT. Heroine of Eternal Blessing. In carrying out its work PT. Srikandi Berkah Abadi did not run smoothly, but there were many obstacles that disrupted the work process, one of which was the data input process. In this research we used a descriptive qualitative method where we carried out observations and direct interviews while conducting KKL within a period of 1 month. Based on the results of research that has been carried out previously, conclusions can be drawn, including: We carry out data processing activities on the implementation of connection work in people's homes, process data input on network maintenance and changes, and input employee hard disk data. While we were carrying out the KKL for 1 month, the problems we experienced were the ones we mentioned above, when inputting data in Microsoft Excel, it often had errors, crashes, and exited so that the data we were working on was lost and not saved.